Brazil's Indians and the onslaught of civilization : the Yanomami and the Kayapó - Rabben, Linda, 1947- (University of Washington Press, 2004)
"The Yanomami and Kayapo, two indigenous groups of the Amazon rainforest, have become internationally known through their dramatic and highly publicized encounters with "civilization." Both groups struggle to transcend internal divisions, preserve their traditional culture, and defend their land from depredation, while seeking to benefit from the outside world. Yet their prospects for the future seem very different. Placing each group in its historical context, Linda Rabben examines the relationship of the Kayapo and Yanomami to Brazilian society and the wider world. She combines academic research with a wide variety of sources, including celebrated leaders Paulinho Payakan and Davi Kopenawa, to assess how each group has responded to outside incursions." "This book is a revised and updated edition of Unnatural Selection: The Yanomami, the Kayapo, and the Onslaught of Civilization, published in 1998"--Jacket